2009
DOI: 10.1373/clinchem.2008.119750
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Receptor LOX-1 Binds to C-Reactive Protein and Mediates Its Vascular Effects

Abstract: Background: C-reactive protein (CRP) exerts biological activity on vascular endothelial cells. This activity may promote atherothrombosis, but the effects of this activity are still controversial. Lectin-like oxidized LDL receptor-1 (LOX-1), the oxidized LDL receptor on endothelial cells, is involved in endothelial dysfunction induced by oxidized LDL. methods: We used laser confocal microscopy to examine and fluorescence cell image analysis to quantify the binding of fluorescently labeled CRP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 40 publications
5
61
0
4
Order By: Relevance
“…We labeled another set of cells with antibodies to Annexin V, CD51, CD61, and CD42. After labeling, samples were analyzed by flow cytometry (29 ). For the EMP measurements, the flow cytometer was kept running for 30 min until the background events were Ͻ1%.…”
Section: Flow Cytometry For Empsmentioning
confidence: 99%
“…We labeled another set of cells with antibodies to Annexin V, CD51, CD61, and CD42. After labeling, samples were analyzed by flow cytometry (29 ). For the EMP measurements, the flow cytometer was kept running for 30 min until the background events were Ͻ1%.…”
Section: Flow Cytometry For Empsmentioning
confidence: 99%
“…In addition, we recently demonstrated that CRP increases vascular permeability through a direct binding to lectin-like oxidized LDL receptor (LOX-1), which is expressed in endothelial cells (10 ). Members of the scavenger receptor family, such as class A scavenger receptor (SR-A), CD36, LOX-1, and scavenger receptor B-I (SR-BI), recognize common ligands such as modified LDL, bacteria, and advanced glycation end products, and they are thought to affect the progression of atherosclerosis (11,12 ).…”
mentioning
confidence: 99%
“…Li et al (10 ) found that CRP may trigger the effects of oxLDL on endothelial cells by upregulating LOX-1. More recently, Fujita et al (11 ) reported that CRP binds to LOX-1-expressing bovine endothelial cells parallel with induction of LOX-1 expression. These observations prompted us to investigate the involvement of CD16, CD32, and LOX-1 in mediating nCRP/mCRP regulation of acetylated LDL (acLDL) uptake.…”
Section: Discussionmentioning
confidence: 99%